Revitalizing Rural Wealth: Uncovering the Potential of Local Resources through Coffee Cake and Jackfruit Cake Innovations for Sustainable Community Development - Riza Mafiroh; Muhammad Junaedi; Silvi Wahyuni; Mukhammad Nur Bakhrul Alam (Universitas Muhammadiyah Sidoarjo, 2024)
The aim of this service is to empower local economic members to build a coffee cake and jackfruit cake business that will increase the income of rural residents, supporting sustainable local economic development. The service method used is joint product development to develop new cake variants with sustainable innovation involving culinary experts, local business actors and the local community. The research results obtained from this service increase local income. Adding production and sales of jackfruit cake and coffee increases the income of rural communities. The implication of this service is strengthening local identity, increasing knowledge about the richness of local culture and making tourists interested in local culinary delights. Therefore, through innovation in coffee cake and jackfruit cake, this project is expected to help sustainable development and welfare of rural communities. Highlights : Joint Collaboration: Involving culinary experts, local businesses, and the community in joint product development fosters collaboration for sustainable innovation. Economic Impact: The introduction of coffee cake and jackfruit cake contributes to increased income, supporting local economic development in rural areas. Cultural Enrichment: The project enhances local identity, promotes cultural richness, and attracts tourists through the innovation in coffee and jackfruit cakes. Keywords : Coffee Cake and Jackfruit Cake, Sustainable Community Development, Rural Wealth, Culinary Diversity, Rural Economic Empowerment